2013
DOI: 10.17660/actahortic.2013.1012.163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 1-MCP and Hot Water Treatment on Postharvest Quality of Pomegranate Fruit

Abstract: Pomegranates are commonly stored in Iran at temperatures higher than 10°C and RH≈70%. At this storage condition, the fruit are affected by desiccation and loss of quality. In this experiment, the effect of Smartfresh TM (1-MCP) at 1 µl L-1 with hot water treatment (HWT) at 50°C for 5 min and the combination of these two treatments (Smartfresh TM +HWT) were studied in reducing the mentioned problems in 'Malas Saveh' pomegranate fruit. Untreated fruit was used as the control. The fruit were stored at 13°C for 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous reports indicated that exposure to 1-MCP may improve the postharvest storage performance of pomegranate fruits. For example, Sepahvand and Ghasemnezhad (2013) reported that exposure to 1-MCP reduced the shriveling index of Iranian 'Malas Saveh' pomegranate fruits after 45 days of storage at 13 C followed by 7 days at 20 C. Other studies, by Defilippi et al (2006) and Zhang et al (2008), indicated that exposure to 1-MCP reduced superficial scald incidence and peel browning of 'Wonderful' and 'Dahongpao' varieties, respectively. Defilippi et al (2006) reported that exposure to 1-MCP at 1 mL L À1 reduced scald incidence of lateseason 'Wonderful' pomegranates after 4 and 5 months of cold storage at 7 C by 60 and 43%, respectively, whereas Zhang et al (2008) reported that 1-MCP reduced the peel browning index of 'Dahongpao' pomegranates after 7 weeks of storage at ambient temperatures by 35%.…”
Section: Pomegranatementioning
confidence: 97%
“…Previous reports indicated that exposure to 1-MCP may improve the postharvest storage performance of pomegranate fruits. For example, Sepahvand and Ghasemnezhad (2013) reported that exposure to 1-MCP reduced the shriveling index of Iranian 'Malas Saveh' pomegranate fruits after 45 days of storage at 13 C followed by 7 days at 20 C. Other studies, by Defilippi et al (2006) and Zhang et al (2008), indicated that exposure to 1-MCP reduced superficial scald incidence and peel browning of 'Wonderful' and 'Dahongpao' varieties, respectively. Defilippi et al (2006) reported that exposure to 1-MCP at 1 mL L À1 reduced scald incidence of lateseason 'Wonderful' pomegranates after 4 and 5 months of cold storage at 7 C by 60 and 43%, respectively, whereas Zhang et al (2008) reported that 1-MCP reduced the peel browning index of 'Dahongpao' pomegranates after 7 weeks of storage at ambient temperatures by 35%.…”
Section: Pomegranatementioning
confidence: 97%
“…For example, exposure to 1‐MCP reduced shriveling in Iranian ‘Malas Saveh’ pomegranate fruits after 45 days of storage at 13 °C followed by 7 days at 20 °C . Other studies have indicated that exposure to 1‐MCP diminishes superficial scald incidence and peel browning and maintains the internal quality of ‘Wonderful’ and ‘Dahongpao’ pomegranate varieties, respectively …”
Section: Introductionmentioning
confidence: 97%
“…Treatment of pomegranate fruit with exogenous ethylene does not elicit any notable effects on organoleptic attributes in postharvest cold storage performance, including peel and juice colour and juice total soluble solids (TSS), titratable acidity (TA) and pH . The main problems associated with postharvest storage of pomegranate fruits are weight loss and shrivelling, decay, CI, superficial scald development and a decrease in flavour acceptability . Previous studies have indicated that exposure to the ethylene inhibitor 1‐methylcyclopropene (1‐MCP) improves the postharvest storage performance of pomegranate fruits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations